Multifunctional Magnetic Nanoparticles for Dynamic Imaging and Therapy. Issue 11 (7th November 2022) - Ko, Min Jun; Hong, Hyunsik; Choi, Hyunjun; Kang, Heemin; Kim, Dong‐Hyun
Abstract : Image‐Guided Therapies In article number 2200053, Heemin Kang, Dong‐Hyun Kim, and co‐workers review the recent advancement in using multifunctional magnetic nanoparticles that enable dynamic motion or degradation or imaging‐guided targeting under a magnetic field. The use of these materials for simultaneous imaging and dynamic magneto‐cell regulation toward tissue engineering, magnetic hyperthermia, ferroptosis, and imaging‐guided therapies is also highlighted in this article.